Application of Remote Sensing Technology in Monitoring the Carbon Dioxide Content in the Atmosphere - Feng, Houhua; Wang, Zeyu; Zhang, Xiangyue (Transactions on Environment, Energy and Earth Sciences, 2024)
Monitoring the carbon dioxide (CO2) concentration in the atmosphere is crucial for reducing carbon emissions. Compared to traditional ground-based monitoring, remote sensing measurements have a wider coverage and stronger continuous monitoring capabilities. This paper introduces the types and characteristics of remote sensing satellites used for CO2 detection, describes the detection process and main technologies, and takes the remote sensing satellite carrying AIRS (Atmospheric Infrared Sounder) as an example to analyze its application in CO2 detection. The results indicate that the current remote sensing satellites have TIROS-N series TOVS sensors, AIRS, IASI, SCIAMACHY, GOSAT, and OCO. The remote sensing technology process includes mission planning and sensor selection, data acquisition, data preprocessing, spectral analysis, inversion algorithm for extracting CO2 concentration information, spatial resolution optimization, data quality control and validation, spatiotemporal analysis and data fusion, generation of visual reports, and data dissemination. The data obtained from the AIRS remote sensing satellite for detecting CO2 concentration has been validated through comparison with ground station and aircraft measurement data. In addition, by analyzing the spatial and temporal distribution of CO2 and analyzing the intensity and seasonal variations of carbon sources and sinks in different regions, high carbon emission areas can be identified. Remote sensing technology also has some challenges and uncertainties, such as limitations caused by atmospheric turbulence, cloud cover, and lower accuracy. Therefore, future research needs to optimize remote sensing data processing methods further, develop more accurate inversion models, and consider integrating multiple remote sensing data sources.